The Relationship Of Pregnant Women's Motivation And Compliance With 3rd Trimester Antenatal Care (ANC) Visits At The Atikah Midwifery Clinic, Penyabasan District, Mandailing Natal District - Khoirunnisa’a Batubara; Ester Selfia Napitupulu (Sean Institute, 2023)
It is very important for pregnant women to have knowledge of the signs and dangers of pregnancy to prevent problems during pregnancy. A good level of knowledge for pregnant women regarding the dangers of pregnancy can motivate themselves and can increase compliance in making ANC visits which affects the quality of life of the mother and child. The aim of this research is the relationship between motivation and compliance with antenatal care (ANC) visits in the third trimester at the Midwife Nur Atikah Sipolu-polu clinic, Payanbungan District, Mandailing Natal Regency in 2023. This type of research is quantitative research with a correlational method. The population in this study was pregnant women and 35 people complied with Antenatal Care (ANC) visits at the Atikah Clinic. The sampling technique uses total sampling. Data collection uses a questionnaire. Data analysis used the chi square test. The results of the study showed that the relationship between pregnant women's motivation and compliance with Antenatal Care (ANC) visits in the third trimester showed that of the 6 respondents who had good motivation, all of them complied with ANC visits, then of the 17 respondents who had good motivation, most of them complied with the visit. ANC as many as 11 people (31.5%). Meanwhile, of the 12 respondents who had less motivation, the majority did not comply with ANC visits. The results of the chi-square statistical test prove that there is a significant relationship between the motivation of pregnant women and compliance with Antenatal Care (ANC) visits in the third trimester at the Midwife Atikah Panyabungan clinic with a p value = 0.021 (p<0.05). The conclusion of this research is that there is a significant relationship between the motivation of pregnant women and compliance with Antenatal Care (ANC) visits in the third trimester at the Atikah Midwife clinic. It is hoped that health workers will provide counseling to pregnant women to comply with Antenatal Care (ANC) visits.